Improving the Performance of Baker's Yeast-powered MFCs by Adding Dehydrogenase Enzymes to Oxidize Yeast-produced Ethanol. Issue 1 (1st March 2022) - Nguyen, Hoang-Uyen-Dung; Trang Nguyen, Dang; Taguchi, Kozo
Abstract: This study focuses on theoretically and experimentally enhancing the performance of a baker's yeast-powered microbial fuel cell (MFC) by hybridizing the MFC and EFC (enzymatic fuel cells) technologies. To improve the power density of the MFC, commercially available alcohol and aldehyde dehydrogenase enzymes (ADHE) have been added to the anode chamber to oxidize ethanol, which is produced by Baker's yeast (BKY) during the metabolic process, to acetic acid. This oxidation process contributes more power output for the MFC. BKY biofilm was formed in porous 3D activated carbon paper to make the anode. The combination of using the biofilm anode and ADHE for electricity generation by the MFC enabled about 19% improvement in the maximum power density if compared with the MFC without using ADHE. Also, aerobic and anaerobic culture conditions were investigated. The result showed that under the anaerobic culture condition, the MFC generated about 22% higher maximum power density than that of the aerobic condition. These results imply that the addition of ADHE can take full advantage of BKY-produced ethanol to boost overall BKY-powered MFC performance.